Picomolar Assay of Native Proteins by Capillary Electrophoresis Precolumn Labeling, Submicellar Separation, and Laser-Induced Fluorescence Detection - Pinto, Devanand M; Arriaga, Edgar A; Craig, Doug; Angelova, Jordanka; Sharma, Neepun; Ahmadzadeh, Hossein; Dovichi, Norman J; Boulet, Camille A (Analytical chemistry (Washington), 1997)
We report a method for the assay of proteins at concentrations lower than 10-10 M with as little as 200 amol of protein. High sensitivity is accomplished by derivatizing the ε-amino group of the protein's lysine residues with the fluorogenic dye 5-furoylquinoline-3-carboxaldehyde and use of a sheath flow cuvette fluorescence detector. Most proteins have a large number of lysine residues; therefore, a large number of fluorescent molecules can be attached to each protein molecule. In general, precolumn labeling improves sensitivity but degrades resolution due to the inhomogeneity of the reaction products from multiple labeling. However, we demonstrate that, through careful manipulation of the separation and reaction conditions, high sensitivity can be obtained without excessive loss in separation efficiency. Over 190 000 theoretical plates are obtained for fluorescently labeled ovalbumin.